Artificial intelligence and games - Yannakakis, Georgios N., author; Togelius, Julian, author (Cham, Switzerland : Springer Intenational Publishing AG, 2018)
'Part I Background -- Introduction -- AI Methods -- Part II Ways of Using AI in Games -- Playing Games -- Generating Content -- Modeling Players -- Part III, The Road Ahead -- Game AI Panorama -- Frontiers of Game AI Research -- References -- Index.
Includes bibliographical references and index.
Keywords: Electronic games -- Programming; Artificial intelligence